Language extinction in process across Chabacano communities: A sociolinguistic approach - Genuino, Cecilia Fortuno (Animo Repository, 2005)
The present study attempted to document the language extinction process of Chabacano across five communities: Zamboanga, Ternate, Cavite City, Davao City and Ermita. More specifically it sought to describe: (1) the language preferred by the speakers in face-to-face oral interaction with different interlocutors in different domains; (2) the factors that motivate the speakers in choosing one language over others; (3) the status of Chabacano and the factors that led the language to its current status; and (4) the possible link between language and age and language and domain. Data were obtained through survey, participant observation, in-depth interview and dyadic recording. A total of 278 individuals who were grouped according to age (70-years old and over, 40-69 years old, 20-39 years old, 5-19 years old) participated in the study. They were chosen through purposive, accidental and snowball sampling techniques. Data gathering lasted for five months. In Zamboanga, Chabacano, Filipino, English, Cebuano and Tausug were in the repertoire of the speakers. Chabacano remained as the most preferred language, followed by Filipino, Cebuano, English, and Tausug. In terms of language attitude, English appeared to be the most prestigious language, followed by Filipino. Cebuano, Chabacano and Tausug. In Ternate, Filipino, English and Chabacano comprised the speech repertoire of the speakers. Filipino was the most preferred language followed by Chabacano and English. In terms of language attitude, English was considered as the most prestigious being the language of education and some formal occasions. Filipino was the second most prestigious language while Chabacano was the least. In Cavite City, Filipino, Chabacano and English were in the repertoire of the first three generations of speakers. The youngest generation knew only Filipino and English. The order of preference was Filipino, followed by Chabacano, followed by English with the first three generations of speakers. With the youngest generation, however, Filipino was more preferred than English. In terms of prestige, Ternate and Cavite City have the same pattern of language attitude where English was the most prestigious followed by Filipino, yet Chabacano was the least. In Davao City and Ermita, Chabacano speech communities are no longer existing. Cebuano and Filipino respectively were generally the language of the speakers in the two communities. In Zamboanga, Ternate and Cavite City, interlocutor was identified as the most important factor influencing language choice. Other factors were age and role-relationship. Topic and place were not considered contributory factors. Chabacano in Zamboanga is surviving, in Ternate and Cavite City, the language is dying. In Davao City and Ermita, the language is dead. The factors that contributed to the stability of Chabacano in Zamboanga were intergenerational language transmission, continuous use of the language in different domains and local government policy. The factors that threatened the survival of the language in three speech communities were: migration, intermarriage, language policy of the national government, economic advancement and language attitude. Finally, the paper maintains that Chabacano is neither safe nor dead in the Philippine setting rather it is in the process of extinction across cultures.